1974
DOI: 10.1136/jnnp.37.10.1162
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma cells in the cerebrospinal fluid in plasma cell neoplasia

Abstract: From Cairo, Egypt SYNOPSIS Myeloma cells were detected in the cerebrospinal fluid of two patients with plasma cell neoplasia during the myelographic studies of 38 patients whose myeloma was associated with extensive neurological complications. The myeloma cells were looked for in Wright stained centrifuged deposit of 2-5 ml samples of the cerebrospinal fluid obtained during myelography. The possibility that occult traumatic lumbar puncture had allowed entry of circulating myeloma cells from the peripheral bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In contrast, infiltration of the leptomeninges in multiple myeloma seems to be rare. We could find only two reported cases (Afifi, 1974;Maldonado et al, 1970).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, infiltration of the leptomeninges in multiple myeloma seems to be rare. We could find only two reported cases (Afifi, 1974;Maldonado et al, 1970).…”
Section: Discussionmentioning
confidence: 82%
“…Meningeal myeloma is presumed to develop as a result of neoplastic proliferation into myeloma cells of the totipotent mesenchymal cells accompanying the pial blood vessels. This mechanism may be held responsible for the development of both isolated meningeal myeloma and meningeal lesions complicating systemic myelomatosis (Afifi, 1974). Cerebral myeloma occurring early in the disease is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Table II shows the case reports of central nervous system in volvement in multiple myeloma. Meningeal infiltration of myeloma cells was diagnosed histologically at the time of autopsy in the cases reported by Ben-Bassat et al [2] and Maldonado et al [5], Afifi [1] reported 2 myeloma patients who had muscle weak ness. Cytological examinations revealed myeloma cell infiltration into the CSF with out plasma cells in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]7,9,[11][12][13][16][17][18][21][22][23]25,27,[29][30][31][32][36][37][38][39][40][42][43][44][45][46] Our case is the 38th. The immunoglobulin types reported involved IgG, IgA, IgD and light chain; our case is the fourth report of light chain myeloma with meningeal involvement.…”
Section: Discussionmentioning
confidence: 99%